Generation of an immortalized astrocytic cell line from Abcd1-deficient H-2KbtsA58 mice to facilitate the study of the role of astrocytes in X-linked adrenoleukodystrophy. Issue 2 (February 2021) - Morita, Masashi; Toida, Ai; Horiuchi, Yuki; Watanabe, Shiro; Sasahara, Masakiyo; Kawaguchi, Kosuke; So, Takanori; Imanaka, Tsuneo
Abstract: X-linked adrenoleukodystrophy (X-ALD) is an inherited metabolic disease characterized by inflammatory demyelination, and activated astrocytes as well as microglia are thought to be involved in its pathogenesis. Conditionally immortalized astrocytic cell clones were prepared from wild-type or Abcd1 -deficient H-2K b tsA58 transgenic mice to study the involvement of astrocytes in the pathogenesis of X-ALD. The established astrocyte clones expressed astrocyte-specific molecules such as Vimentin, S100β, Aldh1L1 and Glast. The conditionally immortalized astrocytes proliferated vigorously and exhibited a compact cell body under a permissive condition at 33 °C in the presence of IFN-γ, whereas they became quiescent and exhibited substantial cell enlargement under a non-permissive condition at 37 °C in the absence of IFN-γ. An Abcd1 -deficient astrocyte clone exhibited a decrease in the β-oxidation of very long chain fatty acid (VLCFA) and an increase in cellular levels of VLCFA, typical features of Abcd1-deficiency. Upon stimulation with LPS, the Abcd1 -deficient astrocyte clone expressed higher levels of pro-inflammatory genes, such as Il6, Nos2, Ccl2 and Cxcl10, compared to wild-type (WT) astrocytes. Furthermore, the Abcd1 -deficient astrocytes produced higher amounts of chondroitin sulfate, a marker of reactive astrocytes. These results suggest that dysfunction of Abcd1 renders astrocytes highly responsive to innate immune stimuli. Conditionally immortalized cell clones which preserve astrocyte properties are a useful tool for analyzing the cellular and molecular pathology of ALD. Abstract : Abcd1; Astrocyte; Immortalized cell; X-linked adrenoleukodystrophy; Peroxisome; Very long chain fatty acid.